Disclosure of Corporate Social Responsibility (CSR) Through Factors that Influence it - Handari, Henni; Yopi Yulius; Ita Reinita Ita Reinita; Idayanti Idayanti (Dinasti Publisher, 2023)
Research on Corporate Social Responsibility has often been carried out, but in this study there is a little novelty, namely the disclosure of Corporate Social Responsibility through the influence of variables Board of Commissioners Size, Institutional Ownership, Public Share Ownership, and Profitability. The population studied is manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2017-2021, using purposive sampling, 15 companies were obtained as samples. Multiple regression analysis method with panel data and secondary data processed with Eviews software version 12.0. Research findings show that the variables of Board of Commissioners size, Institutional Ownership, Public Share Ownership, and Profitability simultaneously affect Corporate Social Responsibility (CSR) disclosure. This research can be used by Issuers to be obliged to publish complete and accurate financial statements in order to provide appropriate information to shareholders, as well as managing profitability in Corporate Social Responsibility disclosure to attract investors.